2014
DOI: 10.1002/cyto.b.21204
|View full text |Cite
|
Sign up to set email alerts
|

Utilility of flow cytometry as ancillary study to improve the cytologic diagnosis of thyroid lymphomas

Abstract: Results: A final diagnosis of lymphoma was given in 13 of 35 (37.1%) specimens. Among the 22 cases considered negative for lymphoma by FC, 11 were diagnosed as thyroiditis by cytology, 7 as reactive, 2 were anaplastic carcinoma, and 2 cases were considered cytologically suspicious for lymphoma but were not confirmed by further investigations. Histology on core biopsy or molecular analysis was available in 12 of 13 lymphoma cases (92.3%). Data obtained by the combination cytology/FC were confirmed in all cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
(52 reference statements)
1
15
0
Order By: Relevance
“…FC has been proven to be of great value when there is a diagnostic dilemma between a hematologic and a reactive or inflammatory condition in which the lymphocyte infiltrate mimics lymphoma [22,23]. Small round blue neoplasms such as neuroendocrine tumors or poorly differentiated Ca and melanoma may be another diagnostic dilemma in which FC can contribute to a differential diagnosis towards lymphomas [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…FC has been proven to be of great value when there is a diagnostic dilemma between a hematologic and a reactive or inflammatory condition in which the lymphocyte infiltrate mimics lymphoma [22,23]. Small round blue neoplasms such as neuroendocrine tumors or poorly differentiated Ca and melanoma may be another diagnostic dilemma in which FC can contribute to a differential diagnosis towards lymphomas [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of FC and FNA produced 97% sensitivity and 87% specificity for the detection of B-lymphomas [41]. In a recent paper we demonstrated that the combination of FC and FNA produces a sensitivity and specificity of 100% in the detection of NHL of the thyroid [42]. Our paper reports the identification of 12 mature B-cell neoplasms (11 B-cell NHL, 1 Burkitt lymphoma, BL) and 1 case of precursor T-lymphoblastic lymphoma (PTLL) among 35 examined samples.…”
Section: Thyroid Lymphoproliferative Processesmentioning
confidence: 99%
“…The literature that we are aware of that reports the use of FC is listed in table 2[29,30,31,32,33,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. Two papers were case reports [48,54]; some included thyroid specimens in studies performed to assess the overall value of FNA in NHL diagnosis [29,30,32].…”
Section: Thyroid Lymphoproliferative Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometry (FC) is a well‐established technique to investigate hemopoietic disorders widely used to evaluate peripheral blood, bone marrow aspirates and body cavity fluids . In our laboratory, it has been successfully applied not only to “natural” fluids, but also in solid tissues after their disaggregation and in fine‐needle aspirates (FNA) of patients with suspected non‐Hodgkin lymphomas (NHL) . During routine FC immunophenotyping activity, we occasionally encountered cells of nonhemopoietic origin, particularly whenever working with FNA and body cavity fluids; the clue of their presence was mostly related to detection of CD45‐negative (CD45−) cell populations often associated to unusual light scatter.…”
Section: Introductionmentioning
confidence: 99%